2010
DOI: 10.1007/s00436-010-1918-7
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis hominis and Dientamoeba fragilis in patients fulfilling irritable bowel syndrome criteria

Abstract: Studies have suggested a possible role for Blastocystis hominis and Dientamoeba fragilis in the etiology of irritable bowel syndrome (IBS). We studied the prevalence of B. hominis and D. fragilis in patients with IBS-diarrhea (IBS-D). Three hundred and thirty patients were enrolled, 171 (52%) with IBS-D and 159 (48%) were controls, respectively. Stool microscopy, culture, and polymerase chain reaction (PCR) for B. hominis and D. fragilis were done. B. hominis was positive by stool microscopy in 49% (83/171) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 22 publications
(38 reference statements)
4
89
3
5
Order By: Relevance
“…Both compare the prevalence of D. fragilis in IBS-patients and controls. 35,36 One study found that D. fragilis was more prevalent in IBS-patients compared with controls (4% versus 0%), 35 whereas the other study showed the exact opposite (2% versus 27%). 36 Methodological differences make the results difficult to compare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both compare the prevalence of D. fragilis in IBS-patients and controls. 35,36 One study found that D. fragilis was more prevalent in IBS-patients compared with controls (4% versus 0%), 35 whereas the other study showed the exact opposite (2% versus 27%). 36 Methodological differences make the results difficult to compare.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical response rate in patients co-infected with Blastocystis was low, and we failed to eradicate D. fragilis and Blastocystis from two patients. Blastocystis has previously been associated to IBS, 27,35,36 and further studies into the relevance of this parasite in IBS are warranted. Because of the limitations of the study no firm conclusions can be made, and results can primarily serve a hypothesis-generating purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectología al Día las mismas técnicas (p < 0,001) 42 . Pese a estos resultados, otros estudios no logran demostrar la asociación entre SII y B. hominis [43][44][45][46] .…”
Section: Artículo Originalunclassified
“…IBS is undoubtedly a heterogeneous disorder and may, indeed, encompass a number of distinct entities (Loftus, 2004). It comes as no surprise, therefore, that over the years a number of factors have been proposed as relevant to the etiopathogenesis of IBS and its various symptoms such as psychological and environmental agents besides infection with different agents (Drossman et al, 2010;Ji et al, 2005;Spiller et al, 2009). Later, studies have described a possible role for protozoan parasites, such as Blastocystosis hominis, Dientamoeba fragilis, and others in the etiology of IBS or IBD (Tungtrongchitr et al, 2004;Yakoob et al, 2010). Hence, it is essential that all patients with IBS undergo routine parasitological investigations in order to rule out the presence of protozoan parasite as the causative agents of clinical signs.…”
Section: Introductionmentioning
confidence: 99%